Mizoroki–Heck Cyclizations of Amide Derivatives for the Introduction of Quaternary Centers. Issue 23 (3rd May 2017) - Medina, Jose M.; Moreno, Jesus; Racine, Sophie; Du, Shuaijing; Garg, Neil K.
Abstract: We report non‐decarbonylative Mizoroki–Heck reactions of amide derivatives. The transformation relies on the use of nickel catalysis and proceeds using sterically hindered tri‐ and tetrasubstituted olefins to give products containing quaternary centers. The resulting polycyclic or spirocyclic products can be obtained in good yields. Moreover, a diastereoselective variant of this method gives access to an adduct bearing vicinal, highly substituted sp 3 stereocenters. These results demonstrate that amide derivatives can be used as building blocks for the assembly of complex scaffolds. Abstract : Adding complexity : A non‐decarbonylative Mizoroki–Heck reaction of Boc‐activated amide derivatives is reported. The transformation relies on the use of nickel catalysis and proceeds using sterically hindered tri‐ and tetrasubstituted olefins to give products containing quaternary centers. The results demonstrate that amide derivatives can be used as building blocks for the assembly of complex scaffolds.